Inovasi Isi Siomay Dengan Porporsi Daging Ayam Dan Tahu Goreng - Divia Nindy Fariza; Lilis Sulandari; Mauren Gita Miranti; Any Sutiadiningsih (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2024)
Chicken Siomay is a food originating from China but is very popular in Indonesia, especially in Menganti Gresik Market, where many siomay sellers are found. Innovation in making siomay using additional proportions of fried tofu is one way to meet consumer needs. The purpose of this study was to determine: 1) determine the best proportion of chicken meat and fried tofu in the contents of chicken siomay dough; 2) the nutritional content of chicken siomay from the best proportion of chicken meat and fried tofu. This type of research is an experiment with three different treatments (75%: 25%, 50%: 50%, 25%: 75%) which were tested on 30 panelists. The results of organoleptic properties were analyzed using a single ANOVA SPSS program and nutritional content was analyzed in the laboratory. The results of data analysis show: 1) The best proportion treatment of the organoleptic test results is the proportion of 50%:50% chicken meat and fried tofu with an average result of chicken siomay shape 3.73 uniform round skin quite pleated, color 3.76 ivory cream, aroma 3.67 quite aromatic chicken siomay less aromatic tofu, texture 3.83 less chewy, taste 3.06, and preference 3.83 quite savory chicken less tofu flavor; 2) the results of laboratory tests of chicken siomay with the proportion of chicken meat and fried tofu are ash content 1.15%, water content 14.86%, protein content 11.92%, fat content 3.02%/100g.